Pendampingan Perancangan dan Deteail Engineering Design (DED) Gedung Serbaguna PCM Sawit Boyolali - Guntur Nugroho; As'at Pujianto; Yoga Aprianto Harsoyo; Fathurrahman Kamal; Gita Danu Pranata; Ghoffar Ismail; Chusnul Azhar; Arini Hidayah; Ulfah Dian Indriyani (Jurnal Pengabdian Masyarakat Nusantara, 2024)
The Community Service Program (PkM) titled "Design of the Multi-Purpose Building at Pimpinan Cabang Muhammadiyah (PCM) Sawit Boyolali" was initiated to address the need for infrastructure in the form of a multi-purpose building. The scope of the activity includes the planning and design of the building so that it can adequately accommodate various activities according to the required capacity and comfort, while also meeting technical building standards. The method used consists of four main stages. First, gathering data on the site, user needs, and the necessary building technical standards. Second, conducting an analysis of space planning and programming. Third, formulating the design concept. Fourth, developing the design into technical drawings or Detailed Engineering Drawings (DED) and preparing a cost estimate (RAB). The final goal of this PkM is to produce a Design Document for the Multi-Purpose Building for PCM Sawit Boyolali.